Preliminary Page: TABLE OF CONTENTS (UNIZIK Journal of STM Education, 2023)
EDITORIAL COMMENTThe Unizik Journal of STM Education publishers reports of empirical research in Science, Technology, Engineering and Mathematics (STEM) Education as well as related studies in education generally. The publication is a medium of communicating well researched works for the science community as a forum for communication and cooperation among STEM teachers and students, policy makers, educators and other educational practitioners across the globe. This sixth edition of the journal contains nineteen (19) articles that have passed through peer-review by professionals. The opinions expressed are not necessarily those of the editorial board but of individual authors. These papers are very informative, educative and instructive and I therefore invite the readers to enjoy reading the contributors. The editorial board of UNIZIK Journal of STM Education appreciates those who subscribe to the journal, reviewers and the consulting editors for their contributions.Dr.N. N. Achufusi-Aka Editor-in-Chief